Involvement of the MiR-181b-5p/HMGB1 Pathway in Ang II-induced Phenotypic Transformation of Smooth Muscle Cells in Hypertension - Fengjuan Li; Cheng-long Zhang; Xiu‐Ju Luo; Jun Peng; Tianlun Yang (2018)
Phenotypic transformation of vascular smooth muscle cells (VSMCs) contributes to vascular remodeling in hypertension. High mobility group box-1 (HMGB1) has been reported to be involved in several pathogenic processes including VSMC proliferation and migration. The present study was designed to determine the role of HMGB1 in VSMC phenotypic transformation in hypertension. First, we demonstrated that HMGB1 was elevated in a model of Ang II-induced VSMC phenotypic transformation, which showed down-regulation of contractile proteins and up-regulation of synthetic proteins. Knockdown of HMGB1 and losartan could block the phenotypic transformation. Next, we identified three potential miRNAs for upstream regulation of HMGB1 by bioinformatic analysis; only miR-181b-5p was significantly down-regulated in Ang II-treated cells. Co-treating the cells with miR-181b-5p mimics suppressed HMGB1 expression as well as the phenotypic transformation, migration, and proliferation. Furthermore, the luciferase reporter gene assay confirmed the direct interaction between miR-181b-5p and HMGB1. Finally, to extend these cell-based studies to clinical patients, we demonstrated that plasma miR-181b-5p levels were decreased, while Ang II and HMGB1 levels, as well as the intima-media thickness (IMT) were increased in hypertensive patients; these effects were reversed following the administration of angiotensin receptor blockers. Based on these observations, we conclude that the down-regulation of miR-181b-5p leads to the elevation of HMGB1 levels in hypertensive patients, which accounts, at least partially, for VSMCs phenotypic transformation and vascular remodeling. Our findings also highlight that the plasma levels of miR-181b-5p and HMGB1 may serve as novel biomarkers for vascular remodeling in the hypertensive patients.